The effect of vision-based exercises on the psychological risk factors affecting falls in the elderly - Dehghani jarje kandi rod, Aref; Nasri, Sadegh; Arazeshi , Negar (Applied Family Therapy Journal (AFTJ), 2020)
Aim: The aim of the current research was the effect of vision-based exercises on the psychological risk factors of falling in the elderly. Method: The current research was of a semi-experimental type with a pre-test-post-test design with a control group and in terms of practical purpose. All the elderly were from Tehran. A statistical sample was prepared by referring to elderly care and welfare centers and a list of elderly people (over 60 years old) in Tehran, and those who were available and willing to participate in the research were purposefully and available in two experimental and control groups of 15 people. Results: The results of covariance analysis showed that in both reaction time and memory variables, the training group achieved better performance than the control group in the post-test. The results of the correlated t-test showed that there were significant changes in the reaction time and memory results from the pre-test to the post-test in the training group (P=0.05). Conclusion: Considering the suitability of vision exercises for the elderly, it is suggested to use these exercises in sports programs to improve the memory and reaction time of the elderly.